Nexus, Volume 4 essays in German Jewish studies - Donahue, William Collins ca. 20./21. Jh; Helfer, Martha B. 1962- (Camden House, 2018)
Features a special section on the Hungarian German Jewish writer and theater director George Tabori and a Forum section on the 2016 film A German Life